Economic and social transformation: The impact of urbanization on the informal worker - W. Wahyudi; O. Sukmana; B. Avianto (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: This research explores the impact of urbanization on informal workers in Surabaya, focusing on street vendors and day laborers. Urbanization in Surabaya has triggered significant economic and social transformations, created new job opportunities, and also increased challenges for informal workers.METHODS: The study employs a qualitative approach using in-depth interviews and participatory observation to collect data from informal workers.FINDINGS: The findings indicate that 78% of informal workers experience significant income volatility, while 65% report facing high competition and 72% lack access to essential resources. To cope, 68% extend their working hours, and 54% utilize social networks for support. Additionally, 61% of respondents benefit from government and non-profit support through training and economic empowerment programs, which has led to a 35% improvement in their skill levels. This study underscores the necessity for inclusive policies, as well as increased support for informal workers, to mitigate urbanization’s challenges and improve their overall quality of life.CONCLUSION: This research is expected to significantly contribute to understanding the dynamics of urbanization and its impact on informal workers, as well as offer practical solutions to improve their quality of life. Community support and optimized government policies can help address these challenges and create a more inclusive and sustainable urban environment.